2016
DOI: 10.3906/tar-1508-59
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis of green gram (Vigna radiata (L.) Wilczek)through morphological and molecular markers

Abstract: Twenty-three genotypes of green gram (Vigna radiata (L.) Wilczek) were collected to determine the extent of genetic diversity through morphological characters as well as random amplified polymorphic DNA (RAPD), inter-simple sequence repeat (ISSR), and simple sequence repeat (SSR) fingerprinting results. Analysis of variance revealed significant mean square values that indicated a substantial degree of genetic variability among the genotypes. Significant genetic variance was observed for days to 50% maturity, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The number of alleles (23) generated by the ten SSR markers analysis were shared among the studied varieties. The CEDG050 marker recorded the highest number of polymorphic alleles (5).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The number of alleles (23) generated by the ten SSR markers analysis were shared among the studied varieties. The CEDG050 marker recorded the highest number of polymorphic alleles (5).…”
Section: Discussionmentioning
confidence: 97%
“…It was then diluted to 20 ng/μl and stored at −20 °C until use. Ten sets of simple sequence repeat (SSR) marker primers developed by Gunjeet [23] were used to amplify the extracted DNA. The primers were selected based on their annealing temperature and the amplicon size of at most 300 base pairs (Table 1).…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Assessment of genetic diversity in the varieties is of immense importance for planning an effective and scientific breeding program for enhancement of crop yield as well as its stability (Chandra et al 2013;Kaur et al 2016). For assessing genetic diversity, molecular markers in addition to the conventional morphological and biochemical markers are powerful tools since they remain unaffected by environmental factors and are independent of tissue or developmental stage of crops (Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…components. Kaur et al (2016) reported the UPGMA dendrogram based on the combined morphological and molecular markers in which the 23 mungbean genotypes were divided into three main clusters, showing a close genetic relationship, which might be due to their close genetic bases [35].…”
Section: Genetic Diversity In Plant Species -Characterization and Conmentioning
confidence: 99%